Conversation Implications in the Stand Up Comedy "Youtuber Many Haters" on Raditya Dika's Youtube Chanel - Puspa Wahyu Kartikasari; Akhmad Sofyan; Agustina Dewi Setyari (International Journal of English and Applied Linguistics (IJEAL), 2023)
Stand Up Comedy is a form of modern comedy art performance. Raditya Dika is an Indonesian comic who is well-known and widely recognized in the world of stand-up comedy. He is also known as a writer, director, and actor. Raditya Dika's comedy style tends to rely on his personal experience and observations of everyday life. He uses a spontaneous, honest, and often absurd storytelling style, which makes the audience laugh. This type of research is descriptive qualitative. This study aims to describe the types of implicatures in the stand-up comedy show "Youtubers Lots of Haters" on Raditya Dika's youtube channel. This study uses the method of free engagement talk, recording, and taking notes. The results of this study indicate that there are 2 types of implicature, namely conventional and non-conventional. the results of the conversational implicature analysis conducted by the author on Raditya Dika's Stand Up Comedy entitled Youtuber Many Haters which aired on December 19 2017 on Raditya Dika's YouTube channel, researchers found conventional implicature and non-conventional implicature. The researcher also found 4 implicature functions, namely Assertive function, Expressive function, Directive function, and Commissive function. However, in this stand-up comedy, the researcher did not find a declarative function because the text is more likely to express the author's emotions, opinions, invitations, or intentions than to convey factual statements.